High Expression of the SH3TC2-DT/SH3TC2 Gene Pair Associated With FLT3 Mutation and Poor Survival in Acute Myeloid Leukemia: An Integrated TCGA Analysis - Yu, Pengfei; Lan, Haifeng; Song, Xianmin; Pan, Zengkai (Frontiers in Oncology, 2020)
Fms-like tyrosine kinase 3 (FLT3) mutation is one of the most common mutations in acute myeloid leukemia (AML). However, the effect of FLT3 mutation on survival is currently still controversial and the leukemogenic mechanisms are still under further investigation. The aim of our study is to identify differentially expressed genes (DEGs) in FLT3-mutant AML and to find crucial DEGs whose expression level is related to prognosis for further analysis. By mining TCGA-LAML dataset, 619 differentially expressed lncRNAs (DElncRNAs) and 1428 differentially expressed mRNAs (DEmRNAs) were identified between FLT3-mutant and FLT3-wildtype samples. Through weighted gene correlation network analysis (WGCNA) and the following Cox proportional hazards regression analysis, we constructed the prognostic risk models to identify the hub DElncRNAs and DEmRNAs associated with AML prognosis. The presence of both SH3TC2 divergent transcript (SH3TC2-DT) and SH3TC2 in respective prognostic risk models promotes us to further study the significance of this gene pair in AML. SH3TC2-DT and SH3TC2 were identified to be coordinately high expressed in FLT3-mutant AML samples. High expression of this gene pair was associated with poor survival. Using logistic regression analysis, we found that high SH3TC2-DT/SH3TC2 expression was associated with FLT3 mutation, high WBC count, intermediate cytogenetic and molecular-genetic risk. AML with SH3TC2-DT/SH3TC2 high expression showed enrichment of transcripts associated with stemness, quiescence and leukemogenesis. Our study suggests that SH3TC2-DT/SH3TC2 gene pair may be a possible biomarker to further optimize AML prognosis and may function in stemness or quiescence of FLT3-mutant leukemic stem cells (LSCs).